2007
DOI: 10.1152/ajprenal.00140.2007
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of tetradecythioacetic acid on the renin-angiotensin system and blood pressure in SHR and 2-kidney, 1-clip hypertension

Abstract: Bivol LM, Berge RK, Iversen BM. Differential effect of tetradecythioacetic acid on the renin-angiotensin system and blood pressure in SHR and 2-kidney, 1-clip hypertension. Am J Physiol Renal Physiol 293: F839-F845, 2007. First published June 27, 2007; doi:10.1152/ajprenal.00140.2007.-The tetradecythioacetic acid (TTA) is a modified fatty acid known to exhibit pleiotropic effects. First, we compared the effect of TTA on the blood pressure in spontaneously hypertensive rats (SHR) with two-kidney, one-clip (2K1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
6
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 32 publications
4
6
0
1
Order By: Relevance
“…In the present study, we have also confirmed that TTA partially prevents the increase of BP in 2K1C rats, as we have shown previously (5,16). The fact that neither indomethacin nor parecoxib has any effect on BP in 2K1C rats further supports that the TTAs effect on BP is at an upstream site, Fig.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, we have also confirmed that TTA partially prevents the increase of BP in 2K1C rats, as we have shown previously (5,16). The fact that neither indomethacin nor parecoxib has any effect on BP in 2K1C rats further supports that the TTAs effect on BP is at an upstream site, Fig.…”
Section: Discussionsupporting
confidence: 92%
“…The control and 2K1C hypertensive groups were fed with standard rat chow (0.25% Na, 14.7% proteins), and the TTA group was fed standard rat chow that was sprayed with TTA dissolved in acetone (9 g TTA dissolved in 1 liter of acetone to 2.7 kg pellet). We have shown previously that TTA and acetone did not interfere with the food intake (5,16).…”
Section: Animalsmentioning
confidence: 77%
See 2 more Smart Citations
“…TTA is known to be a stimulator of all three types of peroxisome proliferator activated receptors (PPARs) (7), but also acts via PPAR-independent pathways (5). It had been shown that TTA attenuates the development of renal hypertension (8,19), but does not affect established genetic high blood pressure, as seen in the spontaneously hypertensive rat (SHR) (8).…”
mentioning
confidence: 99%